Sleep, premenstrual mood disorder, and women's health. (August 2020) - Meers, Jessica M; Nowakowski, Sara
Highlights: Subjective and objectively measured sleep varies across the normal menstrual cycle. Those with premenstrual mood disorders perceive their sleep as particularly impaired. Difficulty sleeping and premenstrual symptoms each increase mood-related symptoms. Poor sleep and circadian misalignment are associated with menstrual cycle irregularity. Future studies of sleep and mood in women must incorporate menstrual phase into their designs. Abstract : Women experience increased vulnerability for both mood and sleep disorders, and the female menstrual cycle represents one fundamental mechanism related to risk. This review evaluates recent literature integrating female reproduction, sleep, and mood. For as many as one third of women, sleep is disrupted premenstrually, and sleep disturbances are particularly prevalent in those with premenstrual mood disorders. Variation in sleep patterns, circadian rhythm alterations, and decreased melatonin secretions due to hormonal fluctuations during the premenstrual phase of the menstrual cycle could explain sleep complaints and have been linked to menstrual irregularity. Menstrual irregularity is also independently associated with increased risk of mood complaints and poor sleep. Therefore, there is growing evidence for the interactional relationships between poor sleep, circadian rhythm disruption, and mood in reproductive-age women, although further research relating to specific mechanisms of risk are needed.